Caratteri architettonici e problematiche conservative dei fronti edilizi ottocenteschi del centro storico fiorentino - Branchi, Maddalena (Restauro Archeologico, 2023)
The historic center of Florence, universally recognized as a monumental unicum, has been inscribed on the UNESCO World Heritage List since 1982. Although the city is generally known worldwide as the cradle of the Renaissance, most of the city walls of the historic center date back to the latest building transformations. Through the study of the main urban transformations carried out under the government of Pietro Leopoldo up to the assignment of Florence as the capital of the kingdom of Italy, this contribution traces the urban evolution of the modern history of Florence and reflects on the image of today’s city, a result of the stratification of the epochs. Furthermore, the contribution collects some examples of recent interventions carried out on the building fronts that allow us to reflect on the issues and criticalities of the conservation and safeguarding of the urban landscape in its totality and complexity.